Asymmetric Acceptors Enabling Organic Solar Cells to Achieve an over 17% Efficiency: Conformation Effects on Regulating Molecular Properties and Suppressing Nonradiative Energy Loss. Issue 4 (18th December 2020) - Gao, Wei; Fu, Huiting; Li, Yuxiang; Lin, Francis; Sun, Rui; Wu, Ziang; Wu, Xin; Zhong, Cheng; Min, Jie; Luo, Jingdong; Woo, Han Young; Zhu, Zonglong; et al.
Abstract: Y6, as a state‐of‐the‐art nonfullerene acceptor (NFA), is extensively optimized by modifying its side chains and terminal groups. However, the conformation effects on molecular properties and photovoltaic performance of Y6 and its derivatives have not yet been systematically studied. Herein, three Y6 analogs, namely, BP4T‐4F, BP5T‐4F, and ABP4T‐4F, are designed and synthesized. Owing to the asymmetric molecular design strategies, three representative molecular conformations for Y6‐type NFAs are obtained through regulating the lateral thiophene orientation of the fused core. It is found that conformation adjustment imposes comprehensive effects on the molecular properties in neat and blend films of these NFAs. As a result, organic solar cells (OSCs) fabricated with PM6:BP4T‐4F, PM6:BP5T‐4F, and PM6:ABP4T‐4F show high power conversion efficiency of 17.1%, 16.7%, and 15.2%, respectively. Interestingly, these NFAs with different conformations also show reduced energy loss ( E loss ) in devices via gradually suppressed nonradiative E loss . Moreover, by employing a selenium‐containing analog, CH1007, as the complementary third component, ternary OSCs based on PM6:BP5T‐4F:CH1007 (1:1.02:0.18) achieve a 17.2% efficiency. This work helps shed light on engineering the molecular conformation of NFAs to achieve high efficiency OSCs with reduced voltage loss. Abstract : Conformation effects of Y6‐type acceptors are systematically studied based on asymmetric design strategies. Z‐shape and W‐shape conformations‐based acceptors can help reduce energy loss in devices through significantly suppressed nonradiative energy loss. Benefiting from the high open‐circuit voltage of BP5T‐4F in the devices, ternary organic solar cells based on PM6:BP5T‐4F:CH1007 achieve a 17.2% efficiency.